3
$\begingroup$

I have a function $y = \sqrt{x^2 + 1}− x$ and I need to prove if it's a Injective function (one-to-one). The function f is injective if and only if for all a and b in A, if f(a) = f(b), then a = b

$\sqrt{a^2 + 1} − a = \sqrt{b^2 + 1} − b$

$\sqrt{a^2 + 1} + b = \sqrt{b^2 + 1} + a$

$(\sqrt{a^2 + 1} + b)^2 = (\sqrt{b^2 + 1} + a)^2$

$a^2 + 1 + b^2 + 2b\sqrt{a^2 + 1} = b^2 + 1 + a^2 + 2a\sqrt{b^2 + 1}$

$2b\sqrt{a^2 + 1} = 2a\sqrt{b^2 + 1}$

$b\sqrt{a^2 + 1} = a\sqrt{b^2 + 1}$

$(b\sqrt{a^2 + 1})^2 = (a\sqrt{b^2 + 1})^2$

$b^2(a^2 + 1) = a^2(b^2 + 1)$

$b^2a^2 + b^2 = a^2b^2 + a^2$

$b^2 = a^2$

$\sqrt{b^2} = \sqrt{a^2}$

$b = \pm a$

then the function is not injective because $b$ in not equal to $a$, but using online solver the function is injective.

$\endgroup$
5
  • 1
    $\begingroup$ Hint: the derivative is always negative. $\endgroup$ – lulu May 10 '16 at 13:03
  • $\begingroup$ The extra solution comes from the squaring. $\endgroup$ – najayaz May 10 '16 at 13:03
  • $\begingroup$ @G-man thanks, could you explain better with an example. Thanks in advance $\endgroup$ – Gianni May 10 '16 at 13:04
  • 1
    $\begingroup$ Your proof is not correct. You showed that $$f(a)=f(b) \Rightarrow a= \pm b$$ but actually you didn't explicitely give an example for $f(a)=f(-a)$. The error arises when you square everything (third line): this is not a reversible step. $\endgroup$ – Crostul May 10 '16 at 13:05
  • $\begingroup$ Even though it may be reasonable to assume f is defined as $f:\mathbb{R} \rightarrow\mathbb{R}$, it is better to be unambiguous by specifying the domain and codomain. $\endgroup$ – Praneet Srivastava May 10 '16 at 14:01
4
$\begingroup$

When you wrote $$2b\sqrt{a^2 + 1} = 2a\sqrt{b^2 + 1}$$ this gave you a new condition : $a$ and $b$ must have same sign. (The square roots are positive). Hence $a^2=b^2$ implies $a=b$ in this case.

$\endgroup$
0
$\begingroup$

Hint: $$y=\sqrt{x^2+1}-x=\frac1{\sqrt{x^2+1}+x}$$ Then $$f(a)=f(b) \Leftrightarrow \frac1{\sqrt{a^2+1}+a}=\frac1{\sqrt{b^2+1}+b}\Leftrightarrow$$ $$\Leftrightarrow \sqrt{a^2+1}+a=\sqrt{b^2+1}+b \Leftrightarrow a=b$$

$f(t)=\sqrt{t^2+1}+t -$ strictly increasing

$\endgroup$
1
  • $\begingroup$ Thanks @Roman83. I am honest to say I did't understand how to simplify $\sqrt{a^2 + 1}$ and $\sqrt{b^2 + 1}$ $\endgroup$ – Gianni May 10 '16 at 13:09

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.